Unlocking Wellness: Pionering IoT Wearable Sensor with The Smart Ring for Body Fatigue Monitoring - Hadi Putri, Dewi Indriati; Irawan, Elysa Nensy; Venica, Liptia; Pratama, Hafiyyan Putra (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2025)
In this study, we present the development and implementation of a low-cost IoT wearable device, the Smart Ring, designed to monitor body fatigue levels. Fatigue, often resulting from energy-draining physical activities, can lead to serious health conditions such as heart attacks, strokes, and asthma. Current devices like smartwatches offer limited functionality in preventing fatigue by merely providing vital sign information. Our Smart Ring aims to bridge this gap by integrating advanced sensors (MAX30100 for heart rate, SpO2, and body temperature) and utilizing fuzzy logic for real-time fatigue level classification. The Smart Ring is paired with an Android application that not only tracks the user's physiological data but also issues alerts and notifications when fatigue thresholds are reached, ensuring timely intervention. The device is designed to be economical and accessible, promoting widespread adoption for better health monitoring in the Society 5.0 era. Preliminary testing with users has demonstrated the effectiveness of the Smart Ring in accurately detecting and categorizing fatigue levels during various activities, supporting its potential as a valuable tool in personal health management. Index Terms— Low-cost, IoT, wearable sensor, body fatigue, the smart ring